The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1090/s1061-0022-08-00996-5
|View full text |Cite
|
Sign up to set email alerts
|

Admissible conditions for parabolic equations degenerating at infinity

Abstract: Abstract. Well-posedness in L ∞ (R n ) (n ≥ 3) of the Cauchy problem is studied for a class of linear parabolic equations with variable density. In view of degeneracy at infinity, some conditions at infinity are possibly needed to make the problem well-posed. Existence and uniqueness results are proved for bounded solutions that satisfy either Dirichlet or Neumann conditions at infinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
(6 reference statements)
2
30
0
Order By: Relevance
“…By the same arguments used in the proof of Theorem 1.1 in [14], it is shown that This proves the result.…”
Section: (I) Let U ∈ C(ir N ) It Is Easily Seen That U Is a Solutionsupporting
confidence: 70%
See 3 more Smart Citations
“…By the same arguments used in the proof of Theorem 1.1 in [14], it is shown that This proves the result.…”
Section: (I) Let U ∈ C(ir N ) It Is Easily Seen That U Is a Solutionsupporting
confidence: 70%
“…By uniqueness results we obtain U R = V R in Q R,T . Then, arguing as in the proof of Theorem 1.2 in [14], it is shown that…”
Section: Hint Of the Proof Of Theorem 28 For Anymentioning
confidence: 86%
See 2 more Smart Citations
“…On the contrary, for n ≥ 3, existence of bounded solutions to problem (1.2), satisfying at infinity some additional conditions, has been proved, if a(x) → 0 sufficiently fast as |x| → ∞ (see [6,13,14,19,21]). Clearly, these existence results imply nonuniqueness of bounded solutions to the Cauchy problem (1.2).…”
Section: Punzo Nodeamentioning
confidence: 99%